Bangunan Pelinggih Merajan Alit Sebagai Inspirasi Penciptaan Karya Seni Lukis - Neode, Haris Candra; Budiaprilliana, Luh; Mustika, I Ketut (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2022)
Merajan Alit is a place of worship in every Balinese Hindu family house. Visual beauty and its close relationship with self-identity and family make the creator interested in visualizing it into painting works. The foundation used was the Alma M. Hawkins method, Exploration, Improvisation, and Forming. Each of these methods contains methods and stages of creation that are applied by MBKM partners. From these methods and successes, six works were produced, entitled; 1) “Kemulan”, 2) “Taksu”, 3) “Aku Ingin Pulang”, 4) “Punggel”, 5) “Mencari Kedalam Diri”, 6) “Happy Family”. In these six works, the creators combine the transfer of technology, skills and knowledge obtained from campuses and partners, so as to create works that are expected to become the characteristics of the creators. With this work, it can be said, Merajan Alit can be a personal trigger because it is very closely related to personal and family identity. The feelings that arise can be very unique and varied so it is very suitable to be visualized as a work of painting. In addition, the use of traditional painting tools is also important because of the ancestral heritage so that it does not become extinct.